Fatty Acid and Transcriptome Profiling of Longissimus Dorsi Muscles between Pig Breeds Differing in Meat Quality - Kaifan Yu, Gang Shu, Fangfang yuan, Xiaotong Zhu, Ping Gao, Songbo Wang, Lina Wang, Qianyun Xi, Shouquan Zhang, Yongliang Zhang, Yan Li, Tongshan Wu, Li Yuan, Qingyan Jiang (International Journal of Biological Sciences, 2013)
Fat and lean pig breeds show obvious differences in meat quality characteristics including the fatty acid composition of muscle. However, the molecular mechanism underlying these phenotypes differences remains unknown. This study compared meat quality traits between Lantang (a Chinese indigenous breed) and Landrace (a typical lean breed). The Lantang pigs showed higher L* values and intramuscular fat content, lower pH45min, pH24h and shear force in longissimus dorsi (LD) muscle than Landrace (P < 0.05). Fatty acid analysis demonstrated the lower monounsaturated fatty acids (MUFA) and higher polyunsaturated fatty acids (PUFA) percentage in Lantang LD than that in Landrace LD (P < 0.05). To further identify candidate genes for fatty acid composition, the transcriptome of LD muscle from the two breeds were measured by microarrays. There were 586 transcripts differentially expressed, of which 267 transcripts were highly expressed in Lantang pigs. After the validation by real-time quantitative PCR, 13 genes were determined as candidate genes for fatty acid composition of muscle, including Stearoyl-CoA desaturase (SCD). Then, a SCD over-expression plasmid was transfected into C2C12 cells to reveal the effect of SCD on the fatty acid composition in vitro. The results showed that SCD over-expression significantly increased PUFA proportion, while reduced that of saturated fatty acids (SFA) in C2C12 cells (P < 0.05). In summary, this study compared the differences of fatty acid composition and transcriptome in two breeds differing in meat quality, and further identified the novel role of SCD in the regulation of PUFA deposition.